Decision modelling for health economic evaluation - Briggs, Andrew H.; Claxton, Karl; Sculpher, Mark J. (Oxford Oxford University Press, 2006)
"This highly practical guide takes the reader through the key principles and approaches of modelling techniques. It begins with the basics of constructing different forms of the model, the population of the model with input parameter estimates, analysis of the results, and progression to the holistic view of models as a valuable tool for informing future research exercises. Case studies and exercises are supported with online templates and solutions.This book will help analysts understand the contribution of decision-analytic modelling to the evaluation of health care programmes"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Health services administration -- Decision making -- Econometric models; Medical economics -- Econometric models